Hawthorn extract inhibited the PI3k/Akt pathway to prolong the lifespan of Drosophila melanogaster. Issue 8 (5th April 2022) - Wang, Yichun; Wang, Huali; Ma, Tianjiao; Liu, Guishan; Feng, Xu; Liu, Xiaozhi; Ma, Xiaofang; Liu, Suwen; Shi, Donglin; Wang, Biao; Kang, Ji; Wang, Hao; et al.
Abstract: HE is a natural extract with strong antioxidant capacity. Drosophila melanogaster was used to explore HE could delay aging in this study. We detected that 3 mg/ml HE could increase stress tolerance (heat, cold, starvation, oxidative stress), reduce intestinal dysfunction, and prolong the lifespan of D. melanogaster . Network pharmacology analysis showed HE could act through the PI3K‐Akt pathway. Meanwhile, HE intervention inhibited the gene expression of InR, PI3K, and Akt‐1, and further increased the gene expression of Atg1, Atg5, Atg8a, and Atg8b. Furthermore, HE inhibited the unnatural propagation of ISCs and increased the number of lysosomes. Supplement with HE may be an effective intervention for aging D. melanogaster . Practical applications: In recent years, diseases that come with aging have seriously affected people's healthy life. Hawthorn is a kind of nutrient‐rich substance that is rich in flavonoids and thus has many potential biological and pharmacological functions. Our results showed that HE has good antioxidant properties and can maintain intestinal homeostasis, which provides a good theoretical basis for the development and research using HE as an effective natural antioxidant for the elderly. Abstract :